Ecological trends in geometrid moth communities along elevational gradients in tropical rainforests with lessons for tropical biodiversity conservation - Toko, Pagi (Jihočeská univerzita, 2023)
The present thesis focuses on the larger theme of the composition of highly diverse insect communities in tropical rainforests, using geometrid moths (Lepidoptera, Geometridae) as a model taxon. In particular, the study examines the structure and alpha diversity of moth communities at different elevations, their beta diversity as their composition responds to ecological trends in elevation gradients, and their regional gamma diversity as two elevation gradients with a separate geological history are compared and analyzed together. First, we examined changes in geometrid community composition along one of the few complete rainforest elevation gradients in the Palaeotropics, spanning from the lowlands to the timberline at 3700 m asl at Mt. Wilhelm. This is a well-studied gradient to explore a range of drivers of community composition along elevational gradients, including climate, the composition of vegetation, and the predation pressure. We used the same sampling protocols along a shorter elevation gradient in the Whiteman Range on the island of New Britain, which is geographically close, but being an oceanic island, it does not have a common geological history with Mt. Wilhelm. This allowed us to examine species turnover between two gradients and local endemism. Finally, the experience with ecological research in Papua New Guinea, in combination with the thesis author coming from an indigenous community of rainforest landowners, led to the examination of the current situation and future trends in rainforest conservation by indigenous communities globally, and particularly in Papua New Guinea.
Ecological trends in geometrid moth communities along elevational gradients in tropical rainforests with lessons for tropical biodiversity conservation
Ecological trends in geometrid moth communities along elevational gradients in tropical rainforests with lessons for tropical biodiversity conservation
Keywords: altitudinal gradient; beta diversity; insect herbivory; Melanesia; predation; species diversity; tropics; conservation; indigenous people; Papua New Guinea; Geometridae; altitudinal gradient; beta diversity; insect herbivory; Melanesia; predation; species diversity; tropics; conservation; indigenous people; Papua New Guinea; Geometridae